Factors Influencing Interest In Entrepreneurship Among Bengkulu University Students Using The Theory Of Planned Behavior - Anggun Kusuma Wardhani; Lela Rospida (UNIVED Press, 2024)
This study involved seventh-semester students of Bengkulu University who are interested in entrepreneurship or already have a business and have taken entrepreneurship courses. The purpose of this study was to identify all the factors that influence students' entrepreneurial interests. Using Google Forms, an online questionnaire of fifty participants was used to collect data. The results of the research conducted using the theory of planned behavior show that the variables of self-efficacy, subjective norms, and need for achievement have a positive and significant influence on the entrepreneurial interest of Bengkulu University students. In other words, the stronger a person's self-efficacy, subjective norms, and need for achievement, the more interested in entrepreneurship they are.